Viagra (Sildenafil citrate) reduced the frequency of epithelial tumors induced by doxorubicin in Drosophila melanogaster - Silva, Samuel Campos; Santos, Juliene César dos; Orsolin, Priscila Capelari (Medicina (Ribeirao Preto), 2018)
Drug consumption is among the leading causes of cancer development. Therefore, it is necessary to investigate the effects of drugs widely consumed in the world, as the case of Viagra® (Sildenafil Citrate - SC). The objective of the study was to evaluate the modulatory effect of SC on the carcinogenicity induced by Doxorubicin (DXR) by the Test for Detection of Epithelial Tumor Clones in Drosophila melanogaster. Two mutant lines (wts and mwh) were used in order to obtain heterozygous wts+/+mwh larvae, which were treated with three concentrations of CS: 10 mM, 20 mM and 40 mM, alone and in combination with doxorubicin. We verified that SC had no carcinogenic effect at the concentrations evaluated alone. In association with DXR, it was provided a reduced effect of tumor-induced, conferring anticarcinogenic role to SC. It is believed that this effect is due to up-regulation of the caspase-dependent apoptosis and the impediment of cell growth promoted by the drug used. Evidence obtained confirms the tumor protective effect attributed to Viagra® under experimental conditions.